The law of innocence - Connelly, Michael, 1956- (New York : Little, Brown and Company, 2020)
Defense attorney Mickey Haller is pulled over by police, who find the body of a client in the trunk of his Lincoln. Haller is charged with murder and can't make the exorbitant $5 million bail slapped on him by a vindictive judge. Mickey knows he's been framed. Now, with the help of his trusted team, he has to figure out who has plotted to destroy his life and why.
Keywords: Haller, Mickey (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Attorney and client -- Fiction; Los Angeles (Calif.) -- Fiction; Legal fiction (Literature); Detective and mystery fiction